Design and simulation of inductive power transfer system using hybrid compensation topologies - Sami, Noor; Al-Badrani, Harith (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
This research addresses the principle of wireless power transfer (WPT). The system is primarily based on inductive power transfer (IPT). IPT is a recent technology that enables electrical power to be transferred between two coils via a magnetic field without the need for physical conductors. This method is particularly useful in applications where conventional wires cannot be used, such as biomedical implants, electric vehicles, and consumer electronics. Existing advances in system design, magnetic materials, and compensation topologies have significantly improved system performance and expanded their application range. Main challenges in IPT systems include improving efficiency and transmission distance. Hybrid compensation techniques in IPT systems have emerged as a promising solution to enhance system stability and power transfer efficiency under varying load conditions. IPT systems ensure highly efficient battery transfer and charging. This paper presents the design and simulation of a 3.7 kW IPT system employing hybrid compensation topologies specifically inductor–capacitor–capacitor/series (LCC/S) and LCC/LCC configurations to enhance power transfer efficiency and maintain zero phase angle (ZPA) operation. The proposed system is simulated using ANSYS Maxwell and MATLAB/Simulink to evaluate voltage gain, resonant behavior, and power output under varying load conditions. The LCC/LCC topology demonstrates superior load-independent ZPA characteristics and improved receiver-side voltage stability. Simulation results confirm that both configurations achieve high efficiency and robust power transfer over an air gap of 100 mm, with the LCC/LCC system showing better tolerance to misalignment. These findings suggest that hybrid compensation topologies are viable candidates for medium-power wireless charging systems in electric vehicles and industrial automation.